Emerging translational research on magnetic nanoparticles for regenerative medicine. (7th October 2015) - Gao, Yu; Lim, Jing; Teoh, Swee-Hin; Xu, Chenjie
<x xml:space="preserve">Abstract</x> This review summarizes current advances, challenges, and future opportunities of magnetic nanoparticles for regenerative medicine.